2014
DOI: 10.1016/j.ijsu.2014.08.387
|View full text |Cite
|
Sign up to set email alerts
|

Age as a risk factor in the occurrence of pneumothorax after transthoracic fine needle biopsy: Our experience

Abstract: Transthoracic needle biopsy (TTNB) of the lung is a well-established technique for diagnosing many thoracic lesions, and is an important alternative to more invasive surgical procedures. Complications of TTNB include pneumothorax, hemoptysis, hemothorax, infection, and air embolism, with the most common complication as pneumothorax. From June 2011 to June 2014 we performed a prospective study of 188 patients who underwent TTNB with CT guidance at University Hospital of Salerno, Italy. Pneumothorax occurred in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
2
8
0
Order By: Relevance
“…Though CPLB is generally well-tolerated, complications of CPLB include pneumothorax, pulmonary hemorrhage (hemoptysis and hemothorax), air embolism, tumor seeding, and infection [19; 30]. Pneumothorax and pulmonary hemorrhage occur most commonly, while other complications are rare [19].…”
Section: Discussionmentioning
confidence: 99%
“…Though CPLB is generally well-tolerated, complications of CPLB include pneumothorax, pulmonary hemorrhage (hemoptysis and hemothorax), air embolism, tumor seeding, and infection [19; 30]. Pneumothorax and pulmonary hemorrhage occur most commonly, while other complications are rare [19].…”
Section: Discussionmentioning
confidence: 99%
“…In single-center studies, older patient age was found to be an independent risk factor for pneumothorax [14,30]. However, some studies showed that the risk peaked in patients in their 60s or 70s [17,31]. These results could be explained by the possibility that relatively few patients who were very elderly or in an inadequate condition to undergo the procedure were included.…”
Section: Plos Onementioning
confidence: 99%
“…Many factors were considered to increase the risk of pneumothorax, such as age over 60 years old, diameter and depth of tumor, puncture of a fissure, chronic obstructive pulmonary disease and emphysema. [2022] In fact, it is difficult to compare complication results of CPLB between published studies due to inconsistent or even contradictory results owing to various biopsy techniques, defined risk factors, statistical methods and baseline characteristics of lung imaging, and puncture experience, suggesting that the incidence of CPLB-induced complications is multivariate and complex. [2325]…”
Section: Discussionmentioning
confidence: 99%